Effects of debris flow composition on runout, depositional mechanisms, and deposit morphology in laboratory experiments. Issue 9 (30th September 2015) - de Haas, Tjalling; Braat, Lisanne; Leuven, Jasper R. F. W.; Lokhorst, Ivar R.; Kleinhans, Maarten G.
Abstract Predicting debris flow runout is of major importance for hazard mitigation. Apart from topography and volume, runout distance and area depends on debris flow composition and rheology, but how is poorly understood. We experimentally investigated effects of composition on debris flow runout, depositional mechanisms, and deposit geometry. The small‐scale experimental debris flows were largely similar to natural debris flows in terms of flow behavior, deposit morphology, grain size sorting, channel width‐depth ratio, and runout. Deposit geometry (lobe thickness and width) in our experimental debris flows is largely determined by composition, while the effects of initial conditions of topography (i.e., outflow plain slope and channel slope and width) and volume are negligible. We find a clear optimum in the relations of runout with coarse‐material fraction and clay fraction. Increasing coarse‐material concentration leads to larger runout. However, excess coarse material results in a large accumulation of coarse debris at the flow front and enhances diffusivity, increasing frontal friction and decreasing runout. Increasing clay content initially enhances runout, but too much clay leads to very viscous flows, reducing runout. Runout increases with channel slope and width, outflow plain slope, debris flow volume, and water fraction. These results imply that debris flow runout depends at least as much on composition as on topography. This study improves understanding of the effects of debris flow composition on runout and may aid future debris flow hazard assessments.